2019
DOI: 10.1080/09168451.2018.1547104
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure analysis and enzymatic characterization of γ-glutamyltranspeptidase from Pseudomonas nitroreducens

Abstract: Theanine (γ-glutamylethylamide) is an amino acid analog that reduces blood pressure and improves immune responses. The ϒ-glutamyltranspeptidase (GGT) from Pseudomonas nitroreducens IFO12694 (PnGGT) has a unique preference for primary amines as ϒ-glutamyl acceptors over standard L-amino acids and peptides. This characteristic is useful for the synthesis of theanine. We used X-ray crystallographic analysis to understand the structural basis of PnGGT’s hydrolysis and transpeptidation reactions and to characterize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…INTRODUCTION γ-Glutamyltransferase (GGT; EC 2.3.2.2) catalyzes the lysis of γ-glutamyl moieties in glutathione or γ-glutamylated compounds and transfers the γ-glutamyl group to acceptors, playing critical roles in the metabolic cycle of glutathione. 1 Its promising potential in the biosynthesis of various γ-glutamyl amino acid derivatives or peptides with high value and relevant physiological functions make GGT very important in the food industry and pharmaceutical field. 2 For instance, γ-glutamyl ethylamide (L-theanine), which is popularly used as a food taste enhancer, is synthesized by GGT via transpeptidation without the addition of ATP.…”
mentioning
confidence: 99%
“…INTRODUCTION γ-Glutamyltransferase (GGT; EC 2.3.2.2) catalyzes the lysis of γ-glutamyl moieties in glutathione or γ-glutamylated compounds and transfers the γ-glutamyl group to acceptors, playing critical roles in the metabolic cycle of glutathione. 1 Its promising potential in the biosynthesis of various γ-glutamyl amino acid derivatives or peptides with high value and relevant physiological functions make GGT very important in the food industry and pharmaceutical field. 2 For instance, γ-glutamyl ethylamide (L-theanine), which is popularly used as a food taste enhancer, is synthesized by GGT via transpeptidation without the addition of ATP.…”
mentioning
confidence: 99%
“…Enzyme assay. The hydrolysis and transpeptidation activities of GGT were measured by spectrophotometric methods and using high-performance liquid chromatography (Hibi et al, 2019). The protein concentrations were determined according to the Lowry method (Lowry et al, 1951).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Pseudomonas nitroreducens GGT (PnGGT) exhibits higher hydrolytic activity than transpeptidase activity despite high sequence similarity with EcGGT (Imaoka et al, 2010). Recent crystallographic studies on PnGGT in complex with Gly-Gly acceptor demonstrated that the binding mode of Gly-Gly in the active site is probably the reason for its reduced activity as an acceptor (Hibi et al, 2019). The terminal amino group of Gly-Gly is oriented opposite to the nucleophilic active center.…”
Section: Substrate Binding Pocketmentioning
confidence: 99%